Wear-resistant and stain-resistant UHPC white decorative board, composition and preparation method

Through the use of stearic acid modified dolomite aggregate and silane modified white auxiliary gelling materials, combined with hot steam curing and grinding curing processes, the application problems of dolomite ore in the preparation of ultra-high performance UHPC white decorative panels are solved, and the performance and cost-effectiveness of high wear and high stain resistance are improved.

CN118754569BActive Publication Date: 2025-03-14ZHEJIANG JIZHU TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411237872.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-03-14
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

How to use the dolomite mine with rich resources, wide distribution and low price to prepare ultra-high performance UHPC white decorative panels to solve the problems of scarce quartz sand resources and high refining costs in traditional methods.

Method used

By using stearic acid modified dolomite aggregate and silane modified white auxiliary gelling material, combined with hot steam curing and grinding curing processes, the water-repellent stain resistance of dolomite aggregate and the mechanical properties of the plate are improved.

Benefits of technology

It has achieved high wear and stain resistance UHPC white decorative panels, with good appearance quality, high strength and high toughness, high density, low water absorption and high compressive strength, which reduces the cost of raw materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention provides a wear-resistant and stain-resistant UHPC white decorative board, a composition and a preparation method; the composition of the wear-resistant and stain-resistant UHPC white decorative board includes, by mass, 89-91 parts of white silicate cement, 8-15 parts of silane-modified white auxiliary cementitious material, 0.5-1.0 parts of organic silicon hydrophobic agent, 100-120 parts of stearic acid-modified white dolomite aggregate, 2.5-4 parts of liquid water reducer, 0.20-0.30 parts of liquid defoamer, 0.10-0.30 parts of anti-cracking fiber, and 18-22 parts of water. The UHPC white decorative board in the present invention has ultra-high performance, and it not only has good appearance quality, but also has excellent characteristics such as high strength and toughness, high density and high wear resistance, strong hydrophobicity and strong stain resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ultra-high performance concrete, and in particular relates to a wear-resistant and stain-resistant UHPC white decorative board, a composition and a preparation method. Background Art

[0002] Ultra-high performance concrete (UHPC) is a new type of cement-based composite material with excellent performance. Its working performance, compressive strength, tensile strength, toughness and durability far exceed those of ordinary concrete. Its color, texture, grain, mechanism and shape can be adjusted during the casting process of components to meet the personalized design requirements of building decorative panels. Therefore, UHPC is very suitable as the basic material for building decorative panels.

[0003] At present, the main raw materials of UHPC white decorative panels are white silicate cement, white quartz sand, white quartz filler and pigments; for example, the Chinese invention patent with authorization announcement number CN115215613B discloses a preparation method and application of pore-free, high-apparent-quality ultra-high-performance concrete decorative panels, and the main raw materials of the pore-free, high-apparent-quality ultra-high-performance concrete provided are white cement, white silica fume, bubbling beads, silica micropowder, titanium dioxide and quartz sand; among them, white cement, white silica fume, bubbling beads, silica micropowder, etc. mainly play a bonding role, quartz sand plays an aggregate supporting role, and titanium dioxide is mainly used to color the panels.

[0004] The main reason why this patent uses quartz aggregate and silicon micropowder is that quartz sand has high strength and hardness, low porosity, and can give the plate products higher mechanical strength and wear resistance; however, high-quality quartz sand resources are scarce and unevenly distributed, and the associated iron-containing minerals are generally yellow. In order to obtain white quartz sand, the mined quartz ore needs to go through water washing, magnetic separation, pickling, crushing, screening and other processes, which not only pollutes the environment but also leads to a higher price for refined quartz sand.

[0005] Dolomite is widely distributed, and the whiteness of the raw ore after rough selection is above 75. After crushing or grinding, it can also be used as aggregate and filler for some building materials; but compared with quartz aggregate, the structure of dolomite aggregate is not very dense, with relatively more pores and softer hardness, so its strength and hardness are not as good as quartz, and it is rarely used in products with high performance requirements. Therefore, how to use dolomite ore, which is rich in resources, widely distributed and low in price, as aggregate and filler for ultra-high performance decorative panels is a technical problem that needs to be solved in the preparation of UHPC white decorative panels.

[0006] In view of this, it is necessary to provide a wear-resistant and stain-resistant UHPC white decorative board, a composition and a preparation method to solve or at least alleviate the technical problem of how to use dolomite to prepare ultra-high performance UHPC white decorative boards. Summary of the invention

[0007] The main purpose of the present invention is to provide a wear-resistant and stain-resistant UHPC white decorative board, a composition and a preparation method, aiming to solve the above-mentioned technical problem of how to use dolomite to prepare ultra-high performance UHPC white decorative boards.

[0008] To achieve the above object, the present invention provides a composition of a wear-resistant and stain-resistant UHPC white decorative board, which comprises, by weight: 89-91 parts of white silicate cement, 8-15 parts of silane-modified white auxiliary cementitious material, 0.5-1.0 parts of organic silicon hydrophobic agent, 100-120 parts of stearic acid-modified white dolomite aggregate, 2.5-4 parts of liquid water reducing agent, 0.20-0.30 parts of liquid defoaming agent, 0.10-0.30 parts of anti-cracking fiber, and 18-22 parts of water;

[0009] The silane-modified white auxiliary gelling material comprises, by weight: 0.9-1.1 parts of silane, 3-5 parts of water, and 9-11 parts of white auxiliary gelling material; wherein the white auxiliary gelling material comprises white dolomite powder and white metakaolin, and the mass ratio of the white dolomite powder to the white metakaolin is 1-2:1;

[0010] The stearic acid modified white dolomite aggregate comprises: white dolomite aggregate soaked in stearic acid solution.

[0011] Furthermore, the method for obtaining the silane-modified white auxiliary gelling material includes: mixing silane and water to obtain a premix; mixing the premix and a white auxiliary gelling material to obtain the silane-modified white auxiliary gelling material; wherein the white auxiliary gelling material is obtained by mixing white dolomite powder and white kaolin.

[0012] Furthermore, the silane in the silane-modified white auxiliary gelling material includes γ-aminopropyltriethoxysilane.

[0013] Furthermore, the method for obtaining the stearic acid modified white dolomite aggregate includes: mixing stearic acid and ethanol solution in a mass ratio of 1:4-6 to obtain the stearic acid solution; placing white dolomite aggregate in the stearic acid solution and mixing for 10-50 minutes, then separating, and drying the separated white dolomite aggregate to obtain the stearic acid modified white dolomite aggregate.

[0014] Furthermore, in the stearic acid-modified white dolomite aggregate, the particle size of the white dolomite aggregate ranges from 0.15 to 0.63 mm.

[0015] Further, the strength grade of the white silicate cement is 42.5 or 52.5;

[0016] The organosilicon water repellent includes: silane water repellent;

[0017] The liquid water reducing agent includes: a polyether polycarboxylic acid water reducing agent having a water reducing rate of not less than 40% and not entraining air;

[0018] The liquid defoamer comprises: a polyether defoamer having the ability to suppress and defoam;

[0019] The anti-cracking fiber includes: modified polyester synthetic fiber with a breaking strength of ≥900MPa and an elastic modulus of ≥10GPa.

[0020] The present invention also provides a method for preparing a wear-resistant and stain-resistant UHPC white decorative board, comprising the steps of:

[0021] S1, obtaining any of the above-mentioned compositions;

[0022] S2, mixing the components in the composition to obtain UHPC wet mortar; then, slurrying and molding the UHPC wet mortar to obtain a molded board;

[0023] S3, after curing the formed plate, trimming and grinding and curing are performed in sequence to obtain a wear-resistant and stain-resistant UHPC white decorative plate.

[0024] Furthermore, the curing process includes: wet curing the formed sheet for 22 to 26 hours; and heat curing the formed sheet at a temperature of 85 to 95° C. for 45 to 50 hours in a hot steam environment.

[0025] Furthermore, the grinding and curing process includes: grinding the surface of the formed plate with a 50-mesh resin grinding wheel, and spraying and curing with a lithium-based curing agent after grinding; then, grinding the surface of the formed plate with 150-mesh, 300-mesh, 500-mesh, 1500-mesh, and 3000-mesh resin grinding wheels in sequence.

[0026] The present invention also provides a wear-resistant and stain-resistant UHPC white decorative board, which is prepared by any of the above-mentioned methods for preparing the wear-resistant and stain-resistant UHPC white decorative board.

[0027] Compared with the prior art, the present invention has at least the following advantages:

[0028] The present invention prepares a highly wear-resistant and highly stain-resistant UHPC white decorative board based on dolomite; the UHPC white decorative board in the present invention has ultra-high performance, and not only has good appearance quality, but also has excellent characteristics such as high strength and toughness, high density and high wear resistance, strong water repellency and strong stain resistance; therefore, the present invention adopts dolomite to replace refined quartz sand, and overcomes the problems existing in the strength, hardness, stain resistance and other aspects of dolomite.

[0029] The present invention modifies dolomite aggregate by using stearic acid so that the stearic acid fills the pores of the dolomite aggregate, thereby enhancing the water-repellent and stain-resistant performance of the system; at the same time, the dolomite aggregate is used to replace the refined quartz sand with high production and transportation costs, so that the raw materials of the UHPC white decorative board are more easily available and the material cost is reduced.

[0030] The present invention adopts silane-modified metakaolin and dolomite powder to form auxiliary cementitious materials. First, silane is hydrolyzed to generate silanol, and the silanol in the silanol reacts with the hydroxyl on the surface of the cementitious material to form chemical adsorption, thereby improving the dispersibility of the cementitious material, reducing the viscosity of the fresh slurry and the self-shrinkage of the hardened body, and improving the volume stability of the UHPC decorative board; secondly, metakaolin and dolomite powder replace part of the cement to effectively improve the particle gradation of the cement paste, making the cement paste structure more compact; at the same time, dolomite powder has a promoting effect on the early hydration of cement, and dolomite powder in water A de-dolomite reaction occurred in the mud-based material, and hydrated calcium aluminate (C3A·CaCO3·11H2O) was generated, which increased the hydration products and reduced the voids. Secondly, under the curing conditions of hot steam curing, Mg-Al hydrotalcite was generated, which effectively improved the strength and corrosion resistance of cement-based materials, prevented the conversion of ettringite (AFt) to monosulfide hydrated calcium aluminate (AFm), and made the mechanical strength of UHPC board products higher and more stable. In addition, silane modification can also improve the hydrophobicity of auxiliary cementitious materials and improve the stain resistance of the board system.

[0031] The present invention reduces the viscosity of UHPC wet mortar by modifying dolomite aggregate and auxiliary cementitious materials, which is beneficial to improving the fluidity (expansion) of the wet mortar, and is beneficial to the discharge of bubbles inside the wet mortar to improve the mortar density (wet mortar density), greatly reducing the number of pores on the surface of the UHPC plate after grinding, and having a beneficial effect on improving the strength of UHPC.

[0032] The present invention adopts a grinding and curing method to process the UHPC white decorative board, thereby improving the appearance quality and surface touch of the UHPC white decorative board. The improvement of the smoothness of the board is very beneficial to the improvement of the stain resistance performance; at the same time, the molecular diameter of the lithium-based curing agent is small and has strong permeability, and can penetrate into the board by 5-8 mm. The active silicate ions contained in it react with calcium hydroxide to generate hydrated calcium silicate, so that the free calcium in the cement hydrate reacts fully, effectively blocks the pores on the concrete surface, greatly improves the surface strength and hardness of the decorative board, and reduces the wettability of the stain liquid. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Furthermore, the technical solutions between the various embodiments of the present invention may be combined with each other, but this must be based on the fact that they can be implemented by ordinary technicians in the field. When the combination of technical solutions is mutually contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0035] When numerical ranges are given in the embodiments, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention are familiar to those skilled in the art and the description of the present invention, and any methods, equipment and materials of the prior art similar or equivalent to the methods, equipment and materials described in the embodiments of the present invention can also be used to implement the present invention.

[0036] The invention provides a composition of a wear-resistant and stain-resistant UHPC white decorative board. The composition comprises, by weight, 89-91 parts of white silicate cement, 8-15 parts of silane-modified white auxiliary cementitious material, 0.5-1.0 parts of organosilicon hydrophobic agent, 100-120 parts of stearic acid-modified white dolomite aggregate, 2.5-4 parts of liquid water reducing agent, 0.20-0.30 parts of liquid defoaming agent, 0.10-0.30 parts of anti-cracking fiber and 18-22 parts of water.

[0037] In terms of weight percentage, the silane-modified white auxiliary gelling material comprises: 0.9-1.1 parts of silane, 3-5 parts of water, and 9-11 parts of white auxiliary gelling material; wherein the white auxiliary gelling material comprises: white dolomite powder and white kaolin, and the mass ratio of the white dolomite powder to the white kaolin is 1-2:1; the silane in the silane-modified white auxiliary gelling material comprises γ-aminopropyltriethoxysilane (KH550).

[0038] The silane-modified white auxiliary gelling material is an auxiliary gelling material with low water demand. The method for obtaining the silane-modified white auxiliary gelling material includes: mixing silane and water, the mixing time can be 10-20 seconds, to obtain a premix; mixing the premix and the white auxiliary gelling material, the mixing time can be 120-180 seconds, to obtain the silane-modified white auxiliary gelling material; wherein the white auxiliary gelling material is obtained by mixing white dolomite powder and white kaolin.

[0039] The modification process of the silane-modified white auxiliary gelling material can be understood as follows: by weight, 0.9-1.1 parts of γ-aminopropyltriethoxysilane (KH550) and 3-5 parts of water are added and stirred evenly for 10-20 seconds; then 9-11 parts of white auxiliary gelling material are added and stirred for 120-180 seconds to obtain the silane-modified white auxiliary gelling material; the white auxiliary gelling material is a premix obtained by evenly mixing white dolomite powder and white kaolin in a mass ratio of 1-2:1.

[0040] The stearic acid modified white dolomite aggregate comprises: white dolomite aggregate soaked in a stearic acid solution; the stearic acid solution can be obtained by mixing stearic acid and ethanol solution in a mass ratio of 1:4-6. The stearic acid-modified white dolomite aggregate is a hydrophobic aggregate. The method for obtaining the stearic acid-modified white dolomite aggregate includes: mixing stearic acid and ethanol solution at a mass ratio of 1:4-6, and obtaining the stearic acid solution after the stearic acid is completely dissolved; placing the white dolomite aggregate in the stearic acid solution and mixing for 10-50 minutes, and then separating, and drying the separated white dolomite aggregate to obtain the stearic acid-modified white dolomite aggregate; wherein the mass ratio of the white dolomite aggregate to the stearic acid solution can be 20-30:100; the volume concentration of ethanol in the ethanol solution is based on the ability to dissolve stearic acid, and can be not less than 75%, specifically 95%; in the stearic acid-modified white dolomite aggregate, the particle size range of the white dolomite aggregate is 0.15-0.63 mm.

[0041] The modification process of the stearic acid-modified white dolomite aggregate can be understood as follows: pouring stearic acid and ethanol solution into a beaker at a mass ratio of 1:4-6, and then stirring with a magnetic stirrer. After the stearic acid is completely dissolved, pouring the white dolomite aggregate and stirring for 10-50 minutes, then filtering out the white dolomite aggregate and placing it in a vacuum drying oven to dry, to obtain the stearic acid-modified white dolomite aggregate.

[0042] In the present invention, the whiteness of white metakaolin is ≥80, the whiteness of white dolomite powder is ≥80, and the whiteness of white dolomite aggregate is ≥75. As an illustration of other raw materials, in the present invention, the whiteness of white silicate cement is ≥87, and the strength grade is 42.5 or 52.5; the organosilicon hydrophobic agent includes: silane hydrophobic agent; the liquid water reducer includes: polyether polycarboxylic acid water reducer with a water reduction rate of not less than 40% and no air entrainment; the liquid defoamer includes: polyether defoamer with anti-foaming and defoaming capabilities; the anti-cracking fiber includes: modified polyester synthetic fiber with a breaking strength of ≥900MPa and an elastic modulus of ≥10GPa, and the diameter of the anti-cracking fiber can be 20μm and the length can be 6mm.

[0043] The present invention also provides a method for preparing a wear-resistant and stain-resistant UHPC white decorative board, comprising the steps of:

[0044] S1, obtaining any of the above-described compositions; that is, preparing the components of the composition in advance.

[0045] S2, mixing the components in the composition to obtain a uniform UHPC wet mortar; then, slurrying and molding the UHPC wet mortar to obtain a molded board.

[0046] S3, after curing the formed plate, trimming and grinding and curing are performed in sequence to obtain a wear-resistant and stain-resistant UHPC white decorative plate.

[0047] The curing process includes: wet curing the formed sheet for 22 to 26 hours; heat curing the formed sheet at 85 to 95°C for 45 to 50 hours in a hot steam environment. Specifically, it can be: after wet curing the formed sheet for 22 to 26 hours, the sheet is moved into a steam curing kiln, hot steam is introduced into the steam curing kiln to increase the temperature and maintain high humidity, the heating rate is 15 to 20°C / h, the curing temperature is 85 to 95°C, and after heat curing for 45 to 50 hours, the temperature is lowered at a rate of 15 to 20°C to room temperature. In the embodiments and comparative examples of the present invention, wet curing is performed at room temperature.

[0048] The grinding and curing process includes: after the trimming, the molded plate is subjected to surface grinding with a 50-mesh resin grinding disc, and after grinding, a lithium-based curing agent is sprayed and cured, and the curing time can be 1 to 3 hours; then, the molded plate is subjected to surface grinding with 150-mesh, 300-mesh, 500-mesh, 1500-mesh, and 3000-mesh resin grinding discs in sequence. That is, the molded plate is subjected to 50-mesh, 150-mesh, 300-mesh, 500-mesh, 1500-mesh, and 3000-mesh resin grinding disc grinding in sequence; wherein, after grinding with a 50-mesh resin grinding disc, a lithium-based curing agent is sprayed and cured.

[0049] The present invention also provides a wear-resistant and stain-resistant UHPC white decorative board, which is prepared by any of the above-mentioned methods for preparing the wear-resistant and stain-resistant UHPC white decorative board.

[0050] In the present invention, a highly wear-resistant and highly stain-resistant UHPC white decorative board is obtained based on the modification of dolomite aggregate and auxiliary cementitious materials, hot steam curing (hot steam ensures curing) and grinding curing of cement-based materials; the present invention uses dolomite aggregate to replace expensive refined quartz sand, and overcomes the problems existing in the strength, hardness, and stain resistance of dolomite aggregate, making it suitable for the production of UHPC white decorative boards. Specifically, the present invention uses white silicate cement as the main cementitious material, modified metakaolin and dolomite powder as auxiliary cementitious materials, supplemented by modified dolomite aggregate and various functional admixtures, and comprehensively utilizes hot steam curing and grinding curing processes to obtain a highly wear-resistant and highly stain-resistant UHPC white decorative board with a dense structure, high strength and high toughness. In terms of effect, the present invention not only has good appearance quality, but also has the characteristics of high strength and high toughness, high density and high wear resistance, strong hydrophobicity and strong stain resistance, water absorption rate ≤0.8%, impact strength ≥30KJ / m 2 , water contact angle ≥145°, compressive strength ≥140MPa, flexural strength ≥20MPa, Mohs hardness reaches level 8, and wear resistance ratio ≥350%.

[0051] The following are specific examples of the present invention:

[0052] In the following examples and comparative examples, unless otherwise specified, all raw materials used are commercially available products.

[0053] The white silicate cement had a whiteness of 87 and a strength grade of 52.5 and was purchased from Aalborg Portland (Anqing) Co., Ltd.

[0054] The whiteness of white kaolin is 80 and the specific surface area is 15m 2 / g, strength activity index is 120, model is K-1100W, purchased from Guangzhou Kaiju New Materials Co., Ltd.

[0055] The whiteness of white silica fume is 81 and the specific surface area is 22m 2 / g, strength activity index is 120, model is NR95, purchased from Wuhan Xinbida New Materials Co., Ltd.

[0056] White dolomite powder passed through 325 mesh sieve (325 mesh undersize), whiteness is 82, density is 2.82g / cm 3 ; The white dolomite aggregate has a particle size range of 0.15 mm to 0.63 mm and a whiteness of 80; the white dolomite powder and the white dolomite aggregate were purchased from Chenzhou Xinjia New Materials Co., Ltd.

[0057] The whiteness of white quartz sand is ≥80, and the SiO2 content is ≥99%; the whiteness of white quartz powder is ≥80, and the SiO2 content is ≥99%, and the white quartz powder passes 325 mesh (325 mesh sieve under); all are purchased from Fengyang County Dongsheng Quartz Sand Co., Ltd.

[0058] The liquid water reducer is a polyether polycarboxylic acid water reducer with a water reduction rate of not less than 40% and no air entrainment, the brand is SPT-180 viscosity-reducing superplasticizer, purchased from Guangzhou Chaosu Building Materials Co., Ltd.

[0059] The liquid defoamer is a polyether defoamer with both antifoaming and defoaming capabilities, with a brand name of DF-8201, purchased from Dongguan Defeng Defoamer Co., Ltd.

[0060] The crack-resistant fiber is a modified polyester synthetic fiber with a diameter of 20 μm, a length of 6 mm, a breaking strength of ≥900 MPa, and an elastic modulus of ≥10 GPa. The model is TMA-06 and is purchased from Ningbo Shike New Materials Co., Ltd.

[0061] The silicone water repellent is Elite powder silane water repellent with the brand name Seal 81, purchased from Nanjing Yaojie Energy Saving Technology Co., Ltd.

[0062] The brand of stearic acid is SA-1810, which was purchased from Wilmar Oil Technology (Dongguan) Co., Ltd.

[0063] The ethanol solution used was 95% alcohol purchased from Foshan Daping Chemical Technology Co., Ltd.

[0064] The brand of γ-aminopropyltriethoxysilane is KH-550, which was purchased from Dongguan Kangjin New Materials Co., Ltd.

[0065] The lithium-based curing agent used is a lithium-based concrete sealing curing agent with a model of LITHSEAL SC, which was purchased from Shibei Chemical (China) Co., Ltd.

[0066] Example 1

[0067] 1. In this embodiment, the composition of the UHPC white decorative board is as follows by weight:

[0068] 90 parts of white silicate cement, 10 parts of silane-modified white auxiliary cementitious material, 1.0 part of silicone hydrophobic agent, 100 parts of stearic acid-modified white dolomite aggregate, 3 parts of liquid water reducer, 0.20 parts of liquid defoamer, 0.20 parts of anti-cracking fiber, and 20 parts of water.

[0069] The silane-modified white auxiliary gelling material is obtained by uniformly stirring 1 part of γ-aminopropyltriethoxysilane (KH550) and 4 parts of water at room temperature for 20 seconds; then, 10 parts of white auxiliary gelling material are added and stirred for 180 seconds to obtain the silane-modified white auxiliary gelling material. The white auxiliary gelling material is a premix obtained by uniformly mixing white dolomite powder and white metakaolin in a mass ratio of 1:1.

[0070] The method for obtaining stearic acid modified white dolomite aggregate is as follows: at room temperature, stearic acid and ethanol solution are poured into a beaker in a mass ratio of 1:5, and then stirred with a magnetic stirrer at a stirring speed of 300r / min; after the stearic acid is completely dissolved, a stearic acid solution is obtained; white dolomite aggregate is poured into the stearic acid solution and stirred for 30 minutes; then, the white dolomite aggregate is filtered and separated, and placed in a vacuum drying oven at 50°C for 8 hours to obtain stearic acid modified white dolomite aggregate; wherein the mass ratio of the white dolomite aggregate to the stearic acid solution is 25:100.

[0071] 2. In this embodiment, the preparation steps of the UHPC white decorative board are as follows:

[0072] S1, obtaining the composition of the wear-resistant and stain-resistant UHPC white decorative board in this embodiment;

[0073] S2, mixing the components in the composition into a uniform UHPC wet mortar according to a proportion; then, evenly spreading the UHPC wet mortar to form a formed board;

[0074] S3, after curing, the formed board is trimmed and ground to obtain a highly wear-resistant and stain-resistant UHPC white decorative board.

[0075] The curing process is as follows: after wet curing for 24 hours, the formed board is moved into a steam curing kiln. Hot steam is introduced into the steam curing kiln to increase the temperature and maintain high humidity. The heating rate is 15°C / h, the curing temperature is 90°C, and hot steam is introduced as required to ensure the curing temperature and humidity. After 48 hours of hot curing, the temperature is lowered at a rate of 20°C / h to room temperature.

[0076] The grinding and curing process is as follows: after trimming, the formed sheet is surface ground with 50 mesh, 150 mesh, 300 mesh, 500 mesh, 1500 mesh, and 3000 mesh resin grinding discs in sequence; among them, after grinding with a 50 mesh resin grinding disc, a lithium-based curing agent is sprayed and cured for 2 hours, and then the subsequent grinding is continued.

[0077] Example 2

[0078] 1. In this embodiment, the composition of the UHPC white decorative board is as follows by weight:

[0079] 90 parts of white silicate cement, 15 parts of silane-modified white auxiliary cementitious material, 0.8 parts of silicone hydrophobic agent, 110 parts of stearic acid-modified white dolomite aggregate, 4 parts of liquid water reducing agent, 0.30 parts of liquid defoaming agent, 0.30 parts of anti-cracking fiber, and 21 parts of water.

[0080] The silane-modified white auxiliary gelling material is obtained by uniformly stirring 1 part of γ-aminopropyltriethoxysilane (KH550) and 4 parts of water at room temperature for 10 seconds; then, 10 parts of white auxiliary gelling material are added and stirred for 150 seconds to obtain the silane-modified white auxiliary gelling material. The white auxiliary gelling material is a premix obtained by uniformly mixing white dolomite powder and white metakaolin at a mass ratio of 2:1.

[0081] The method for obtaining stearic acid modified white dolomite aggregate is as follows: at room temperature, stearic acid and ethanol solution are poured into a beaker in a mass ratio of 1:5, and then stirred with a magnetic stirrer at a stirring speed of 300r / min; after the stearic acid is completely dissolved, a stearic acid solution is obtained; white dolomite aggregate is poured into the stearic acid solution and stirred for 30 minutes; then, the white dolomite aggregate is filtered and separated, and placed in a vacuum drying oven at a temperature of 50°C for 8 hours to obtain stearic acid modified white dolomite aggregate; wherein the mass ratio of the white dolomite aggregate to the stearic acid solution is 20:100.

[0082] 2. In this embodiment, the preparation steps of the UHPC white decorative board are the same as those in Embodiment 1.

[0083] Example 3

[0084] 1. In this embodiment, the composition of the UHPC white decorative board is as follows by weight:

[0085] 90 parts of white silicate cement, 8 parts of silane-modified white auxiliary cementitious material, 0.5 parts of silicone hydrophobic agent, 120 parts of stearic acid-modified white dolomite aggregate, 3.5 parts of liquid water reducing agent, 0.20 parts of liquid defoaming agent, 0.20 parts of anti-cracking fiber, and 20 parts of water.

[0086] The silane-modified white auxiliary gelling material is obtained by uniformly stirring 1 part of γ-aminopropyltriethoxysilane (KH550) and 4 parts of water at room temperature for 20 seconds; then, 10 parts of white auxiliary gelling material are added and stirred for 180 seconds to obtain the silane-modified white auxiliary gelling material. The white auxiliary gelling material is a premix obtained by uniformly mixing white dolomite powder and white metakaolin at a mass ratio of 1.5:1.

[0087] The method for obtaining stearic acid modified white dolomite aggregate is as follows: at room temperature, stearic acid and ethanol solution are poured into a beaker in a mass ratio of 1:5, and then stirred with a magnetic stirrer at a stirring speed of 300r / min; after the stearic acid is completely dissolved, a stearic acid solution is obtained; white dolomite aggregate is poured into the stearic acid solution and stirred for 30 minutes; then, the white dolomite aggregate is filtered and separated, and placed in a vacuum drying oven at a temperature of 50°C for 8 hours to obtain stearic acid modified white dolomite aggregate; wherein the mass ratio of the white dolomite aggregate to the stearic acid solution is 25:100.

[0088] 2. In this embodiment, the preparation steps of the UHPC white decorative board are the same as those in Embodiment 1.

[0089] Example 4

[0090] 1. In this embodiment, the composition of the UHPC white decorative board is as follows by weight:

[0091] 90 parts of white silicate cement, 12 parts of silane-modified white auxiliary cementitious material, 1.0 parts of silicone hydrophobic agent, 108 parts of stearic acid-modified white dolomite aggregate, 3.0 parts of liquid water reducing agent, 0.30 parts of liquid defoaming agent, 0.20 parts of anti-cracking fiber, and 21 parts of water.

[0092] The silane-modified white auxiliary gelling material is obtained by uniformly stirring 1 part of γ-aminopropyltriethoxysilane (KH550) and 4 parts of water at room temperature for 15 seconds; then, 10 parts of white auxiliary gelling material are added and stirred for 150 seconds to obtain the silane-modified white auxiliary gelling material. The white auxiliary gelling material is a premix obtained by uniformly mixing white dolomite powder and white metakaolin at a mass ratio of 1:1.

[0093] The method for obtaining stearic acid modified white dolomite aggregate is as follows: at room temperature, stearic acid and ethanol solution are poured into a beaker in a mass ratio of 1:5, and then stirred with a magnetic stirrer at a stirring speed of 300r / min; after the stearic acid is completely dissolved, a stearic acid solution is obtained; white dolomite aggregate is poured into the stearic acid solution and stirred for 30 minutes; then, the white dolomite aggregate is filtered and separated, and placed in a vacuum drying oven at a temperature of 50°C for 8 hours to obtain stearic acid modified white dolomite aggregate; wherein the mass ratio of the white dolomite aggregate to the stearic acid solution is 30:100.

[0094] 2. In this embodiment, the preparation steps of the UHPC white decorative board are the same as those in Embodiment 1.

[0095] Comparative Example 1

[0096] 1. In this comparative example, the composition of the UHPC white decorative board is as follows by weight:

[0097] 90 parts of white Portland cement, 10 parts of white silica fume, 30 parts of white quartz sand with a particle size of 0.30mm-0.60mm, 70 parts of white quartz sand with a particle size of 0.15mm-0.30mm, 4 parts of liquid water reducing agent, 0.30 parts of liquid defoaming agent, 1.0 parts of silicone water repellent, 0.15 parts of anti-cracking fiber, and 20 parts of water.

[0098] 2. In this comparative example, the preparation steps of the UHPC white decorative board are as follows:

[0099] S1, obtaining the composition of the wear-resistant and stain-resistant UHPC white decorative board in this comparative example;

[0100] S2, mixing the components in the composition into a uniform UHPC wet mortar according to a proportion; then, evenly spreading the UHPC wet mortar to form a formed board;

[0101] S3, the formed sheets are cured and trimmed in turn, and the surface is cleaned to obtain highly wear-resistant and highly stain-resistant UHPC white decorative sheets.

[0102] The curing process is as follows: after wet curing for 24 hours, the formed board is moved into a steam curing kiln. Hot steam is introduced into the steam curing kiln to increase the temperature and maintain high humidity. The heating rate is 15°C / h, the curing temperature is 90°C, and hot steam is introduced as required to ensure the curing temperature and humidity. After 48 hours of hot curing, the temperature is lowered at a rate of 20°C / h to room temperature.

[0103] Comparative Example 2

[0104] Compared with Example 1, the silane-modified white auxiliary cementitious material in this comparative example is adjusted to a white auxiliary cementitious material, and the stearic acid-modified white dolomite aggregate is adjusted to a white dolomite aggregate; wherein the white auxiliary cementitious material and the white dolomite aggregate are the same as those in Example 1.

[0105] 1. In this comparative example, the composition of the UHPC white decorative board is as follows by weight:

[0106] 90 parts of white silicate cement, 10 parts of white auxiliary cementitious material, 1.0 part of silicone water repellent, 100 parts of white dolomite aggregate, 3 parts of liquid water reducing agent, 0.20 parts of liquid defoaming agent, 0.20 parts of anti-cracking fiber, and 20 parts of water.

[0107] 2. In this comparative example, the preparation steps of the UHPC white decorative board are as follows:

[0108] S1, obtaining the composition of the wear-resistant and stain-resistant UHPC white decorative board in this embodiment;

[0109] S2, mixing the components in the composition into a uniform UHPC wet mortar according to a proportion; then, evenly spreading the UHPC wet mortar to form a formed board;

[0110] S3, after curing, the formed board is trimmed and ground to obtain a highly wear-resistant and stain-resistant UHPC white decorative board.

[0111] The curing process is as follows: after wet curing for 24 hours, the formed board is moved into a steam curing kiln. Hot steam is introduced into the steam curing kiln to increase the temperature and maintain high humidity. The heating rate is 15°C / h, the curing temperature is 90°C, and hot steam is introduced as required to ensure the curing temperature and humidity. After 48 hours of hot curing, the temperature is lowered at a rate of 20°C / h to room temperature.

[0112] The grinding and curing process is as follows: after trimming, the formed sheet is surface ground with 50 mesh, 150 mesh, 300 mesh, 500 mesh, 1500 mesh, and 3000 mesh resin grinding discs in sequence; among them, after grinding with a 50 mesh resin grinding disc, a lithium-based curing agent is sprayed and cured for 2 hours, and then the subsequent grinding is continued.

[0113] Comparative Example 3

[0114] Compared with Example 1, the grinding and curing process was omitted in this comparative example.

[0115] 1. In this comparative example, the composition of the UHPC white decorative board is as follows by weight:

[0116] 90 parts of white silicate cement, 10 parts of silane-modified white auxiliary cementitious material, 1.0 part of silicone hydrophobic agent, 100 parts of stearic acid-modified white dolomite aggregate, 3 parts of liquid water reducer, 0.20 parts of liquid defoamer, 0.20 parts of anti-cracking fiber, and 20 parts of water.

[0117] The silane-modified white auxiliary gelling material is obtained by uniformly stirring 1 part of γ-aminopropyltriethoxysilane (KH550) and 4 parts of water at room temperature for 20 seconds; then, 10 parts of white auxiliary gelling material are added and stirred for 180 seconds to obtain the silane-modified white auxiliary gelling material. The white auxiliary gelling material is a premix obtained by uniformly mixing white dolomite powder and white metakaolin in a mass ratio of 1:1.

[0118] The method for obtaining stearic acid modified white dolomite aggregate is as follows: at room temperature, stearic acid and ethanol solution are poured into a beaker in a mass ratio of 1:5, and then stirred with a magnetic stirrer at a stirring speed of 300r / min; after the stearic acid is completely dissolved, a stearic acid solution is obtained; white dolomite aggregate is poured into the stearic acid solution and stirred for 30 minutes; then, the white dolomite aggregate is filtered and separated, and placed in a vacuum drying oven at 50°C for 8 hours to obtain stearic acid modified white dolomite aggregate; wherein the mass ratio of the white dolomite aggregate to the stearic acid solution is 25:100.

[0119] 2. In this comparative example, the preparation steps of the UHPC white decorative board are as follows:

[0120] S1, obtaining the composition of the wear-resistant and stain-resistant UHPC white decorative board in this embodiment;

[0121] S2, mixing the components in the composition into a uniform UHPC wet mortar according to a proportion; then, evenly spreading the UHPC wet mortar to form a formed board;

[0122] S3, after curing, the formed board is trimmed to obtain a highly wear-resistant and stain-resistant UHPC white decorative board.

[0123] The curing process is as follows: after wet curing for 24 hours, the formed board is moved into a steam curing kiln. Hot steam is introduced into the steam curing kiln to increase the temperature and maintain high humidity. The heating rate is 15°C / h, the curing temperature is 90°C, and hot steam is introduced as required to ensure the curing temperature and humidity. After 48 hours of hot curing, the temperature is lowered at a rate of 20°C / h to room temperature.

[0124] Comparative Example 4

[0125] Compared with Example 1, the white auxiliary cementitious material in this comparative example is adjusted to a premix obtained by uniformly mixing white quartz powder and white metakaolin in a mass ratio of 1:1.

[0126] 1. In this comparative example, the composition of the UHPC white decorative board is as follows by weight:

[0127] 90 parts of white silicate cement, 10 parts of silane-modified white auxiliary cementitious material, 1.0 part of silicone hydrophobic agent, 100 parts of stearic acid-modified white dolomite aggregate, 3 parts of liquid water reducer, 0.20 parts of liquid defoamer, 0.20 parts of anti-cracking fiber, and 20 parts of water.

[0128] The silane-modified white auxiliary gelling material is obtained by uniformly stirring 1 part of γ-aminopropyltriethoxysilane (KH550) and 4 parts of water at room temperature for 20 seconds; then, 10 parts of white auxiliary gelling material are added and stirred for 180 seconds to obtain the silane-modified white auxiliary gelling material. The white auxiliary gelling material is a premix obtained by uniformly mixing white quartz powder and white metakaolin in a mass ratio of 1:1.

[0129] The method for obtaining stearic acid modified white dolomite aggregate is as follows: at room temperature, stearic acid and ethanol solution are poured into a beaker in a mass ratio of 1:5, and then stirred with a magnetic stirrer at a stirring speed of 300r / min; after the stearic acid is completely dissolved, a stearic acid solution is obtained; white dolomite aggregate is poured into the stearic acid solution and stirred for 30 minutes; then, the white dolomite aggregate is filtered and separated, and placed in a vacuum drying oven at 50°C for 8 hours to obtain stearic acid modified white dolomite aggregate; wherein the mass ratio of the white dolomite aggregate to the stearic acid solution is 25:100.

[0130] 2. In this comparative example, the preparation steps of the UHPC white decorative board are as follows:

[0131] S1, obtaining the composition of the wear-resistant and stain-resistant UHPC white decorative board in this embodiment;

[0132] S2, mixing the components in the composition into a uniform UHPC wet mortar according to a proportion; then, evenly spreading the UHPC wet mortar to form a formed board;

[0133] S3, after curing, the formed board is trimmed and ground to obtain a highly wear-resistant and stain-resistant UHPC white decorative board.

[0134] The curing process is as follows: after wet curing for 24 hours, the formed board is moved into a steam curing kiln. Hot steam is introduced into the steam curing kiln to increase the temperature and maintain high humidity. The heating rate is 15°C / h, the curing temperature is 90°C, and hot steam is introduced as required to ensure the curing temperature and humidity. After 48 hours of hot curing, the temperature is lowered at a rate of 20°C / h to room temperature.

[0135] The grinding and curing process is as follows: after trimming, the formed sheet is surface ground with 50 mesh, 150 mesh, 300 mesh, 500 mesh, 1500 mesh, and 3000 mesh resin grinding discs in sequence; among them, after grinding with a 50 mesh resin grinding disc, a lithium-based curing agent is sprayed and cured for 2 hours, and then the subsequent grinding is continued.

[0136] Analysis example 1

[0137] The performance testing methods in each embodiment and comparative example are as follows:

[0138] 1. Apparent density of UHPC wet mortar: The apparent density of UHPC wet mortar is tested in accordance with JGJ / T 70-2009 "Standard for Test Methods for Basic Properties of Building Mortar".

[0139] 2. The expansion, compressive strength and flexural strength of UHPC wet mortar are tested in accordance with T / CECS 10107-2020 "Technical Requirements for Ultra-High Performance Concrete (UHPC)".

[0140] 3. The impact strength of UHPC white decorative panels is tested in accordance with GB / T 15231-2008 "Test method for properties of glass fiber reinforced cement".

[0141] 4. The water absorption rate of UHPC white decorative panels is tested in accordance with T / CBMF 172-2022 "Ultra-High Performance Concrete (UHPC) Decorative Products".

[0142] 5. Test method for water contact angle of UHPC white decorative board: Cut the decorative board into 300mm×400mm×h (h is the thickness of the decorative board) test specimens. After the specimens are cured, use 300# sandpaper to polish the surface of the specimens to prepare a surface roughness structure. Use a rubber-tipped dropper to drop water on the polished surface of the specimens to measure the surface contact angle using a video optical contact angle meter (OCA15 PLUS).

[0143] 6. Mohs hardness test method of UHPC white decorative board: Use a set of reference materials with different hardness levels to compare the scratches with the tested UHPC decorative board to determine the hardness level of the tested UHPC decorative board.

[0144] 7. The wear resistance of UHPC white decorative panels is tested in accordance with JC / T 906-2002 "Cement-based wear-resistant materials for concrete floors".

[0145] 8. The number of pores on the surface of UHPC white decorative board is determined by visual inspection, observation and counting of the number of pores with a diameter ≥ 0.30 mm within a range of 1m×1m on the board surface.

[0146] The performance of the UHPC wet mortar and the performance of the UHPC white decorative board in each embodiment and each comparative example were tested, and the test results are shown in Table 1.

[0147] Table 1 Performance test results

[0148]

[0149] The above technical solutions of the present invention are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the contents of the present invention specification under the technical concept of the present invention, or directly / indirectly applied in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. A composition of a wear-resistant and stain-resistant UHPC white decorative board, characterized in that: Calculated by mass, it includes: 89-91 parts of white silicate cement, 8-15 parts of silane-modified white auxiliary cementitious material, 0.5-1.0 parts of organic silicon hydrophobic agent, 100-120 parts of stearic acid-modified white dolomite aggregate, 2.5-4 parts of liquid water reducing agent, 0.20-0.30 parts of liquid defoaming agent, 0.10-0.30 parts of anti-cracking fiber, and 18-22 parts of water; The silane-modified white auxiliary gelling material comprises, by weight, 0.9-1.1 parts of silane, 3-5 parts of water, and 9-11 parts of white auxiliary gelling material; wherein the white auxiliary gelling material comprises white dolomite powder and white metakaolin, and the mass ratio of the white dolomite powder to the white metakaolin is 1-2:1; The method for obtaining the silane-modified white auxiliary gelling material comprises: mixing silane and water for 10 to 20 seconds to obtain a premix; mixing the premix and the white auxiliary gelling material for 120 to 180 seconds to obtain the silane-modified white auxiliary gelling material; wherein the white auxiliary gelling material is obtained by mixing white dolomite powder and white metakaolin; The stearic acid modified white dolomite aggregate comprises: white dolomite aggregate soaked in stearic acid solution; in the stearic acid modified white dolomite aggregate, the particle size range of the white dolomite aggregate is 0.15-0.63 mm; The method for obtaining the stearic acid modified white dolomite aggregate comprises: mixing stearic acid and ethanol solution at a mass ratio of 1:4-6 to obtain the stearic acid solution; placing white dolomite aggregate in the stearic acid solution and mixing for 10-50 minutes, then separating, and drying the separated white dolomite aggregate to obtain the stearic acid modified white dolomite aggregate.

2. The composition of the wear-resistant and stain-resistant UHPC white decorative board according to claim 1, characterized in that: The silane in the silane-modified white auxiliary gelling material includes γ-aminopropyltriethoxysilane.

3. The composition of the wear-resistant and stain-resistant UHPC white decorative board according to claim 1, characterized in that: The strength grade of the white silicate cement is 42.5 or 52.5; The organosilicon water repellent includes: silane water repellent; The liquid water reducing agent includes: a polyether polycarboxylic acid water reducing agent having a water reducing rate of not less than 40% and not entraining air; The liquid defoamer comprises: a polyether defoamer having the ability to suppress and defoam; The anti-cracking fiber includes: modified polyester synthetic fiber with a breaking strength of ≥900MPa and an elastic modulus of ≥10GPa.

4. A method for preparing a wear-resistant and stain-resistant UHPC white decorative board, characterized in that: Includes steps: S1, obtaining the composition according to any one of claims 1 to 3; S2, mixing the components in the composition to obtain UHPC wet mortar; then, slurrying and molding the UHPC wet mortar to obtain a molded board; S3, after curing the formed plate, trimming and grinding and curing are performed in sequence to obtain a wear-resistant and stain-resistant UHPC white decorative plate.

5. The method for preparing the wear-resistant and stain-resistant UHPC white decorative board according to claim 4, characterized in that: The curing process includes: wet curing the formed sheet for 22 to 26 hours; and heat curing the formed sheet at a temperature of 85 to 95° C. for 45 to 50 hours in a hot steam environment.

6. The method for preparing the wear-resistant and stain-resistant UHPC white decorative board according to claim 4, characterized in that: The grinding and curing process includes: grinding the surface of the formed plate with a 50-mesh resin grinding wheel, spraying and curing with a lithium-based curing agent after grinding; then, grinding the surface of the formed plate with 150-mesh, 300-mesh, 500-mesh, 1500-mesh, and 3000-mesh resin grinding wheels in sequence.

7. A wear-resistant and stain-resistant UHPC white decorative board, characterized in that: The wear-resistant and stain-resistant UHPC white decorative board is prepared by the preparation method of any one of claims 4 to 6.

Citation Information

Patent Citations

  • Preparation method and application of non-porous, high-apparent-quality, ultra-high-performance concrete decorative panels

    CN115215613B